DECREASED BACK PAIN IN TRIMESTER III PREGNANT WOMEN DUE TO PREGNANCY EXERCISE IN SIDOMULYO HEALTH CENTER OF PEKANBARU IN 2019 - Vitriani, Okta; Harahap, Juraida Roito; Novance, Putri Aida (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2020)
Abstract Based on Pekanbaru City Health Profile data in 2017, the coverage ofpregnant women's visits at Sidomulyo Health Center was 1.985. The results ofa preliminary survey at Sidomulyo Health Center found 80% of pregnantwomen experienced back pain. One of the non-pharmacological methods toreduce back pain during pregnancy is pregnancy exercise. This study aimedto determine the decrease in back pain in third trimester pregnant women withpregnancy exercise. This study used a pre-experimental designconducted inSidomulyo Community Health Center Pekanbaru from March to June 2019.The population was trimester III pregnant women who came to check theirpregnancy at the Sidomulyo Health Center in March-May 2019 with a samplesize of 15 taken using purposive sampling technique. Data collection was doneby assessing the back pain of pregnant women before and after pregnancyexercise. The results showed that the average back pain before pregnancyexercise was 3.87, whereas after pregnancy exercise was 1.73. There was adecrease in pain intensity after pregnancy exercise (p = 0.001). It isexpected that midwives should be able to conduct counseling especially inthird trimester pregnant women to do pregnancy exercises